Manajemen Inovasi Pendidikan Inklusif Sebagai Implementasi TQM di MI Al-Mahabbah - Ahmad Syawal; Sutrisno; Suwadi; Musdalifa (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study analyzes the management of inclusive education innovation at MI Al-Mahabbah as an organic implementation of Total Quality Management (TQM) in addressing teacher competency gaps. Using a qualitative instrumental case study approach, data were collected through in-depth interviews with two shadow teachers and the principal, as well as an analysis of adaptive curriculum documents. The results indicate that the four TQM principles (Customer Focus, Continuous Improvement, Employee Involvement, and Leadership Commitment) are implemented in a bottom-up manner through an individualized sensory curriculum (1:1 ratio in separate classes), a weekly evaluation cycle, collaboration among shadow teachers, and freedom to innovate, resulting in increased teacher practical competency and increased participation of students with special needs. However, this model is segregated and vulnerable due to its reliance on personal leadership and the lack of special education competencies. This study confirms the potential of informal TQM as a temporary solution amidst resource constraints, while emphasizing the need for formal training and a collaborative transition to inclusive learning.